Atuação da Igreja de Jesus Cristo dos Santos dos Últimos Dias na recepção de migrantes venezuelanos recém-chegados: um estudo sobre a precarização do trabalho migrante em uma cidade média do interior de São Paulo - Teodoro, Giovana Miorim (Universidade Federal de São Carlos, 2023)
The aim of this article is to explore ways in which non-ethnic migrants are incorporated into their country of destination, focusing on the issue of work as one of the main forms of insertion into the new society. To this end, the empirical basis of the study will be the case of Venezuelan migrants in Brazil who have been internalized by the Church of Jesus Christ of Latter-day Saints (Mormons). In this way, the proposed reflection goes through the general panorama of the performance of religious organizations in the governance of the migratory flow, as well as the relationship between migration and religion, especially in the context of medium-sized cities. In this sense, the text seeks to understand how the incorporation of Venezuelan migrants in Brazil through precarious work is related to the idea of self-sufficiency that members of the aforementioned church highly disseminate.
The role of the Church of Jesus Christ of Latter-day Saints in receiving newly arrived Venezuelan migrants: a study on the precariousness of migrant work in a medium-sized city in the interior of São Paulo state
Keywords: Interiorização; Migrações; Organização religiosa; Governança migratória; Cidade média; Venezuelanos; CIENCIAS HUMANAS::SOCIOLOGIA